O perfil socioeconômico e a profissionalização do motofretista como fatores do comportamento e segurança no trânsito urbano no município de Pelotas/RS - Mascarenhas, Maria Angélica Bueno D' Avila (2017)
Cities are the stage of permanent economic, social, and political contradictions. Amidst the urban traffic, motorcycles become just another player in the competition for space among pedestrians, cyclists, car drivers, trucks, and buses. Due to the high incidence of accidents involving motorcycles, the need arose to study and understand the participation of the motorcycle courier in these occurrences. Composing a fleet in growing expansion, only in thestate of Rio Grande do Sul, in the period of 2011 to 2015, there was a 20% increase inthe motorcycle fleet. This study aims to determine the trained motorcycle courier professional´s profile in the city of Pelotas/RS, contrasting sociocultural aspects, lifestyle, and behavior in traffic, with the incidence of involvement in accidents and violations, characterizing this way, the role of these professionals in urban mobility behavior, its risks, and other features. The methodology of this work began with the survey of the number of motorcycle couriers trained by the specialized course and with a license from the Municipality of Pelotas. The next step consisted of the application of a structured questionnaire with thirty-two questions involving socioeconomic, professional, behavioral characteristics and urban mobility. Soon after, the data obtained with the statistics of DETRAN/RS, Military Brigade and Pelotas Transport and Transit Secretariat were compared. The results showed that the driver is not the main cause of traffic accidents, his posture and behavior in traffic are satisfactory, as this corroborates with the statistics of the supervisory bodies, and they share the idea that for a safer transit, such as the maintenance of roads and signaling, constant investments in the education and supervision of drivers of vehicles are also necessary.